2017
DOI: 10.1038/cdd.2017.108
|View full text |Cite
|
Sign up to set email alerts
|

Differential requirements for Tousled-like kinases 1 and 2 in mammalian development

Abstract: The regulation of chromatin structure is critical for a wide range of essential cellular processes. The Tousled-like kinases, TLK1 and TLK2, regulate ASF1, a histone H3/H4 chaperone, and likely other substrates, and their activity has been implicated in transcription, DNA replication, DNA repair, RNA interference, cell cycle progression, viral latency, chromosome segregation and mitosis. However, little is known about the functions of TLK activity in vivo or the relative functions of the highly similar TLK1 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(58 citation statements)
references
References 50 publications
5
52
1
Order By: Relevance
“… 7 Tlk2 -null mice were embryonically lethal due to placental failure. 15 In this study, we found several predicted LOF variants in affected individuals. To investigate whether variants resulted in an aberrant transcript, we synthesized cDNA from RNA extracted from fibroblast or lymphoblastoid cell lines ( Supplemental Subjects and Methods , Table S7 ) from three individuals with different variants: (1) c.989C>A (p.Ser330 ∗ ), predicted to result in a truncated product leading to nonsense-mediated decay (NMD); (2) c.2092C>T (p.Arg698 ∗ ), with a premature stop codon in the last exon predicted to escape from NMD; and (3) c.1720+1G>T, a mutation predicted to affect splicing of exon 18.…”
Section: Main Textmentioning
confidence: 49%
“… 7 Tlk2 -null mice were embryonically lethal due to placental failure. 15 In this study, we found several predicted LOF variants in affected individuals. To investigate whether variants resulted in an aberrant transcript, we synthesized cDNA from RNA extracted from fibroblast or lymphoblastoid cell lines ( Supplemental Subjects and Methods , Table S7 ) from three individuals with different variants: (1) c.989C>A (p.Ser330 ∗ ), predicted to result in a truncated product leading to nonsense-mediated decay (NMD); (2) c.2092C>T (p.Arg698 ∗ ), with a premature stop codon in the last exon predicted to escape from NMD; and (3) c.1720+1G>T, a mutation predicted to affect splicing of exon 18.…”
Section: Main Textmentioning
confidence: 49%
“…Further evidence on TLK2 autophosphorylation comes from the thesis work of Helena Gonzalez Buron (University of Barcelona, Spain) who confirmed that the residue S 635, located in the TLK2 activation loop, is a crucial TLK2 autophosphorylation site and could be required for TLK2 activity. However, further cellular assays are necessary to validate its functional relevance 35 . Since the kinase domain is highly conserved between TLK1/1B and TLK2, we predict a corresponding residue in TLK1/1B may be involved in its activation and autophosphorylation.…”
Section: Resultsmentioning
confidence: 99%
“…It is interesting that two structural homologues have neurological or immunological roles, maybe as a result of both systems being highly adaptable and evolutionarily and developmentally interlinked [ 68 , 69 ]. TLK2 , another differentially expressed gene is required for placental development and, while coupling with TLK1 , supports genomic stability in mice by recovery of damaged DNA in preparation for mitosis [ 70 , 71 ]. When coupled with ASF1 , TLK2 restores chromatin structure after DNA damage and assists further progression through the cell cycle [ 71 ].…”
Section: Resultsmentioning
confidence: 99%